The use of dating apps in Malaysia / Nur Qistina Daniel Adam...[et al.] - Daniel Adam, Nur Qistina; Mohd Rashidan, Ryhana; Che Rahim, Muhammad Al'lias; Ar Azman, Aini; Mohamad Shukor, Farhanah Izzati; Mohd Fadzil, Ayu Farhanis (Faculty of Communication & Media Studies, 2020)
This research is conducted to investigate the use of dating apps nowadays in this uprising era particularly in Malaysia. The method used is by applying quantitative research by answering a short survey consisted of 40 questions. Dating apps is an alternative way for people to communicate and find their love interest nor just to meet new people. This research is conducted to study regarding the effectiveness of dating apps in Malaysia. Based on the results and findings, it indicates that the level of acceptance towards dating apps in Malaysia is low (M= 2.27). Same goes to the effectiveness of datings apps in Malaysia which is also low (M=2.36) and the level of dating apps usage is also recorded as low (M=2.41). So, throughout this study, dating apps is still not effective in Malaysia (M=2.35).